PENGARUH BIMBINGAN KELOMPOK DAN EFIKASI DIRI TERHADAP PENGETAHUAN DAN TINDAKAN SISWA SMP NEGERI 8 BANDA ACEH DALAM MENGHADAPI BENCANA GEMPA BUMI - Emalia Nuranda; Sri Adelila Sari; Sri Milfayetty; M. Dirhamsyah (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2014)
Abstract: The purpose of this study was to determine the effect of guidance groups and self efficacy to students’ knowledge and action of SMPN 8 BandaAceh in facing the earthquake. This study used a quasi-experimental research method approach. Student preparedness data was collected using a questionnaire. The study population was all students of Junior High School 8 (SMP N 8) Banda Aceh, Indonesia. Samples were selected using purposive of class VII-5, as many as 10 students were given guidance group. Data were analyzed using regression analysis. The results showed that the students knowledge and action of SMPN 8 BandaAceh in facing the earthquake can be increased through group counseling and self-efficacy by 1, 041 % . This means that 98. 96 % contributed by other factors . Keywords: Guidance group, self-efficacy, knowledge, action and earthquakes